The Effect of Work Motivation, Work Competence, and Work Environment on Employee Performance at PT. Sipatex Putri Lestari - Ari Hidayat*; Darwin Nahwan (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this study was to determine the effect of work motivation, work competence, and work environment on employee performance at PT Sipatex Putri Lestari. This research uses descriptive research with a quantitative approach. The population in this study were all employees of PT Sipatex Putri Lestari, a total of 1,900 employees. The sample used was 95 respondents with a sampling technique using probability sampling. The data collection technique used was a questionnaire distributed to employees of PT Sipatex Putri Lestari using a five-point Likert scale as a measuring tool. From this study, it is known that: (1) The variable of work motivation has a positive and significant effect on the performance of employees of PT Sipatex Putri Lestari. (2) Work competency variables have a positive and significant effect on the performance of employees of PT Sipatex Putri Lestari; (3) The work environment variable has a positive and significant effect on the performance of employees of PT Sipatex Putri Lestari